Characterization of soils of Talaulim watershed, North Goa and their suitability for cashew production - Kumar, K.S. Anil; Nair, K.M.; Gaddi, A.V. (Journal of Plantation Crops, 2011)
Talaulim watershed, North Goa located between 15º 27’ N to 15º 29’ N latitude and 73º 53’ E to 73º 55’ E longitude with an elevation of 2 to 90 m MSL, represents land area typical of West Coast as well as midlands and western foot slopes of Western Ghats, supposed to be ideal for cashew-growing. The climate is humid tropical with mean annual rainfall 2932 mm and temperature 27.3 ºC. A high intensity soil survey (1:5000 scale) was carried out in the watershed to characterize the land and soils. The data generated was used to assess the suitability for growing of cashew in those lands. The climatic characteristics like high rainfall, high mean annual temperature and appreciable dry season favour the growing of the crop. Slope (0-5 %), coarse fragments (0-60 % by volume), soil depth (>75 cm), AWC (> 75 mm/m), pH (5.5-7.5) and high organic carbon (> 0.8 %) are the congenial land qualities for cashew. The survey results revealed that, out of 597 ha surveyed, 133.7 ha (22.4 %) is highly suitable, 287.2 ha (48.1 %) moderately suitable and only 2.0 ha (0.3 %) marginally suitable. The remaining area of 65.7 ha (11.0 %) apart from marshy land (10.8 %), water body (4 %), salt pan (2.6 %) and settlements (0.8 %) is unsuitable. Interspersing cashew in the originally forested, but slightly degraded landscape is viable from soil conservation point of view